273. Emergence of the SARS-CoV-2 Omicron Variant in the Pragmatic Assessment of Influenza Vaccine Effectiveness in the Department of Defense (PAIVED) Study. (15th December 2022) - Richard, Stephanie A; Berjohn, Catherine M; Collins, Limone; Seshadri, Srihari; Spooner, Christina; Campbell, Wesley R; Ganesan, Anuradha; Fries, Anthony C; Hrncir, David; Lalani, Tahaniyat; Warkentien, Tyler; Markelz, Ana E; et al.
Abstract: Background: Novel SARS-CoV-2 (SCV2) variants may differ in epidemiology and clinical impact. PAIVED, a randomized trial comparing the efficacy of 3 different platforms of inactivated influenza vaccines in adult military health system beneficiaries, actively surveils participants for influenza-like illness (ILI), including COVID-19, and conducts targeted investigations among those who develop ILI. The current season (2021/22) offered an opportunity to assess symptomatology associated with emerging SCV2 variants in this prospective cohort. Methods: Following receipt of influenza vaccine, PAIVED participants receive a weekly email or text message querying for ILI symptoms. Those who reported ILI completed a validated symptom diary (FLU-PRO Plus) daily for 7 days and collected a nasal swab. Nasal specimens underwent multiplex PCR testing, followed by SCV2 genome sequencing as applicable. PAIVED study participants from the 2021-22 influenza season who reported an ILI, had confirmed infection with SCV2 for which sequence data is available, and completed at least one FLU-PRO Plus survey were included in this analysis. Results: To date, 293 participants (7% of active cohort; 22.5% reporting ILI) tested positive for SCV2; sequencing has identified 23 Delta and 200 Omicron variants (199 BA.1, 1 BA.2). Among the 212 participants with sequenced SCV2 and symptom data, 55% were male, 57% were white, and 85% were active-duty military (Table 1). Overall, peak symptom severity was classified as mild to moderate in 79.3% of cases, fever duration averaged 2.5±2.2 days, and there were activity limitations for a mean of 5.2±3.8 days. No differences in maximum symptom scores (total or by domain) were detected for participants infected with Omicron compared to Delta. Figure 1 depicts variation in mean symptom scores by day of ILI, grouped by variant. Table 1. Demographic characteristics of PAIVED study participants with Delta and Omicron SARS-CoV-2 variants during the 2021/22 season. Figure 1. Mean FLU-PRO Plus domain and total scores by days since identification of an influenza-like illness in participants with Omicron or Delta variants of SARS-CoV-2 in the 2021/22 season of PAIVED. Conclusion: Omicron emerged as the predominant SCV2 variant causing ILI in our cohort this season, typically manifesting with mild symptoms. Further exploration of potential differences in ILI experience between SCV2 variants and other ILI causes, plus the impact and timing of vaccination, will add insight into the relative contribution of such factors on symptomatology. Disclosures: John H. Powers, III, MD, Arrevus: Advisor/Consultant|Eicos: Advisor/Consultant|Evofem: Advisor/Consultant|Eyecheck: Advisor/Consultant|Gilead: Advisor/Consultant|GlaxoSmithKline: Advisor/Consultant|OPKO: Advisor/Consultant|Resolve: Advisor/Consultant|Romark: Advisor/Consultant|SpineBioPharma: Advisor/Consultant|UTIlity: Advisor/Consultant|Vir: Advisor/Consultant Jitendrakumar Modi, MD, GlaxoSmithKline: I am a paid speaker for GSK. I do not speak for their flu brand. Timothy Burgess, MD, MPH, AstraZeneca: The HJF, in support of the USU IDCRP, was funded to conduct or augment unrelated Phase III Mab and vaccine trials as part of US Govt. COVID19 response.